Analisis Faktor-Faktor yang Berpengaruh Terhadap Return Saham pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Sub Sektor Makanan dan Minuman yang Tercatat Aktif di Bursa Efek Indonesia Periode 2013-2017 - Dionisius Sole (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research aims to examine and analyze the factors that influence stock returns in manufacturing companies in the consumer goods and food sub-sector listed on the Indonesia Stock Exchange (IDX). The independent variables in this research are Earning Per Share (EPS), Price Earning Ratio (PER), Return On Assets (ROA), and Firm Size. The dependent variable in this research is stock returns. The number of observations in this research were 55 of 11 companies multiplied by 5 years. This research uses purposive sampling method. Empirical results in this research using the SPSS program using multiple linear regression analysis methods. The results of this reserach indicate that return on assets (ROA) has a significant effect on stock returns. While earnings per share (EPS), price earning ratio (PER), and firm size have no significant effect on stock returns. These results indicate that investors should pay attention to return on assets (ROA) in their investment strategies. As well as looking at the small effect of the independent variables on the dependent variable, it is suggested the need for caution in generalizing the results of this research.